A Socio-Linguistic Profile of Nigeria’s Eastern Borderlands - Otora Osmond Agbor; Angela Ajimase (Tamaddun Life, 2022)
The paper examines the phenomena of language maintenance, shift, separation, and spread of the demographic proportion of the ethnolinguistic groups on either side of the borders, and argues that language use in various public domains is consistent with language policy, planning, and development. The paper is anchored on visible data in a conceptual framework that offers a triglottic configuration that has been used in both and within various multilingual states in Africa, and more specifically with Cameroon by Tadedjeu (1975) and Nigeria by Brann (1981). The Tadedjeu and Brann framework enabled an analysis of the border configuration concerning languages. It is indicated that the seemingly autochthonous peoples of the border are so deeply rooted that it appears most of them wandered there within the last few centuries. Thus, with the growing level of interdependence across the border region, it is considered that the younger generation of the border peoples will someday wander into cities, become bilingual, and forget their language, leaving behind a vanishing generation of chthonophones.